Afirmasi Partai Politik Meningkatkan Partisipasi Perempuan: Sebuah Studi di Kabupaten Sumenep - Ikmal, Moh (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
The purpose of this study is to find out how the affirmative action of political parties in encouraging women?s political participation in Sumenep Regency. This study uses descriptive qualitative research with data collection procedures in the form of interviews, observation and documentation. Data validation techniques used are source triangulation techniques in the form of person and paper. The results show that the efforts made by political parties of Sumenep Regency in building women?s political participation include, 1) parties taking an internal/personal approach; 2) programmatic, structured and continuous development of the political model of female cadres; 3) hold meetings at times that are possible to be attended by female cadres and times that are not too preoccupied with household needs.